State of the art of passenger redirection during incidents in public transport systems, considering capacity constraints - Frederik R. Bachmann; Antonios Tsakarestos; Fritz Busch; Klaus Bogenberger (Public Transport, 2023)
Abstract This paper gives a comprehensive insight into the investigations done in passenger redirection during incidents in public transport systems. In public transport operations, incidents such as traffic accidents, deployment of emergency forces, or technical failures happen every day and disrupt the service. Most of the investigations done in the field of incident management focus on the readjustment of the supply towards the incident situation and are therefore referred to as supply-centric part of incident management. However, especially in recent years, more and more investigations have also been done on the passenger-centric part of incident management. These rather focus on the effects of incidents on passengers or even include them in the solution of the incident situation, either by informing them adequately about the given situation (passive redirection) or by providing them with concrete path advice (active redirection). The results show that adequate passenger information during incidents can reduce the average delay of affected passengers and support the recovery of the public transport system. This improves the reliability of a public transport system and boosts its attractiveness.
Keywords: 330; Public transport; Passenger redirection; Incident management; Disruption; Literature review